PENGARUH TINGKAT KEAKTIFAN PENGGUNAAN JEJARING SOSIAL TERHADAP PERILAKU KONSUMTIF SISWA SMAN 9 SURABAYA DALAM BERBELANJA ONLINE - PUPUT KURNIAWATI, YULIA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Nowadays the internet is one of communication and information media which widely used by the majority of people. Through the Internet, people can accessing the information and communicating in a flexible, fast, and economical. Even through the internet, anyone can simplify the buying and selling process by online shopping. The internet site which are much-loved today is social networking.The purpose of this research is to find out the influence of social networking activeness on online shopping consumptive behaviour in students of SMAN 9 Surabaya. This research uses a quantitative approach with a population is students of class X and XI which have a social networking accounts and have been online shopping. The sample are 180 respondents conducted by cluster sampling technique. The data was collected by questionnaires. Simple linear regression, t-test and test for normality was used to analyze the data.The results showed a significant degree of influence between social networking activeness on online shopping consumptive behaviour with value of tcount is 2,135 and the significance of value are 0,034. The using level activity of social networking influence of 2.5% on online shopping consumptive behaviour and in the category of very low. Keywords: social networking, consumptive behavior, online shopping